Innovación en la orientación universitaria: la mentoría como respuesta - Andrés Valverde Macías; Covadonga Ruiz de Miguel; Eduardo García Jiménez; Soledad Romero Rodríguez (Universidad de La Rioja, 2013)
The present article shows the important role that mentoring can wield as a guidance strategy at University. To do so, the starting point is the needs analysis of the university student body in their first year and the description of the situation of the guidance services in the University, so as to support the idea of the benefits of mentoring in helping the student in general, and in his transition to the University specifically. Afterwards, the characteristics that enclose mentoring (concept, objectives, models, advantages and disadvantages) are approached, as well as the process followed in its development (the mentoring cycle). Some university experiences, both international and national, are also described. Finally, as a conclusion, the key elements for the success of mentoring at University are discussed, as well as the elements that prevent its development.